Exploring the Determinants of Poverty Gap in Sumatra Island: A Spatial Regression Approach - Shalma, Euis; Ratih Yulihar Taher, Arivina (Lafadz Jaya Publisher, 2025)
The poverty gap index is an important indicator in planning more effective and targeted policies, but it has rarely been studied. This study analyzes the distribution pattern of poverty gap and the influence of non-food per capita expenditure, open unemployment rate, and Gini ratio on poverty gap in districts/municipalities in Sumatra Island in 2023. Using cross-section data from 154 districts/municipalities, the analysis was conducted through the calculation of the global Moran index and spatial autoregressive (SAR) regression. The results show that the gap of poverty in Sumatra Island has a clustered spatial pattern. Regions with moderate to high poverty gap are concentrated in the northern, southern, and western islands, especially in Aceh, Bengkulu, South Sumatra, Lampung, and Nias, Mentawai, and Meranti Islands. In contrast, the central part of Sumatra tends to have lower poverty gap. From the regression analysis, non-food per capita expenditure has a negative effect and Gini ratio has a positive effect on poverty gap. These findings emphasize the importance of considering spatial factors in the formulation of poverty alleviation policies in Sumatra.